Chiroptical spectroscopy and metabolomics for blood-based sensing of pancreatic cancer - Habartová, Lucie; Bunganič, Bohuš; Tatarkovič, Michal; Zavoral, Miroslav; Vondroušová, Jana; Syslová, Kamila; Setnička, Vladimír (Chirality, 2018)
To enable the early diagnosis of pancreatic cancer, the search for and definition of reliable biomarkers remain a subject of great interest, with the specificity and sensitivity of the currently used biomarkers being below the required values. We tested a novel diagnostic approach for pancreatic cancer based on the specific molecular signature of blood plasma components. To acquire more detailed structural information, structure-sensitive chiroptical methods (electronic circular dichroism and Raman optical activity) were supplemented by conventional Raman and infrared spectroscopies. The obtained spectra were subsequently processed by linear discriminant analysis yielding high values of specificity and sensitivity. In addition, to monitor not only large biomolecules as potential biomarkers but also those of low molecular weight, we conducted an analysis of blood plasma samples by using metabolomics. The achieved results suggest a panel of promising biomarkers for a reliable detection of pancreatic cancer.
Keywords: senioři; karnitin; Spectrum Analysis, Raman; cirkulární dichroismus; spektroskopie infračervená s Fourierovou transformací; metabolomika; Metabolomics; lidé; diskriminační analýza; Middle Aged; chiroptical spectroscopy; studie případů a kontrol; nádory slinivky břišní; pancreatic cancer; Lysophosphatidylcholines; Discriminant Analysis; Biomarkers, Tumor; Spectroscopy, Fourier Transform Infrared; blood plasma; nádorové biomarkery; Humans; Circular Dichroism; spectral biomarker; Pancreatic Neoplasms; lysofosfatidylcholiny; pilotní projekty; lidé středního věku; Raman spectroscopy; metabolomics; Pilot Projects; Aged; Ramanova spektroskopie; Carnitine; Case-Control Studies